Pengaruh Model PBL Dan Inkuiri Terbimbing Terhadap Prestasi Belajar Siswa Ditinjau Dari Berpikir Kritis Siswa - Khaerus Syahidi; Tsamarul Hizbi; Laela Alfizair (Kappa Journal, 2019)
This research purposed to knowing: 1) the influence of probleb based learning anda guided inquiry models toward student learning achievement, 2) the influence of high and low critical thinking toward student learning achievement, 3) the intraction between problem based learning and guided inquiry  models with critical thinking on student learning achievement. The population in this study were all students of class XI IPA MA Mualimat NW Pancor academic year 2018/2019. The study sample was determined by cluster random sampling technique with class XI IPA 2 as an experimental class while class X IPA 3 as a control class. The design of this study uses factorial 2x2. Data collection techniques using questionnaires and tests. Data is analyzed using two-way anava. The results showed, 1) there was an influence of learning model of problem based learning and guided inquiry on physics learning achievement because of FAcount> Ftable, ie. 75,778> 3,99, which means H0A was rejected, 2) there was the influence of high critical thinking and critical thinking low on student physics learning achievements because FB count> Ftable is 22.421> 3.99, 3) there is no interaction between problem based learning and guided inquiry with students' critical thinking on student physics learning achievement because FAB count <Ftable is -68.992 <3.99.